Monitoring and enforcement of environmental regulations. Lessons from a natural field experiment in Norway - Kjetil Telle (Statistics Norway, Research Department, 2012)
Relying on a small natural field experiment with random assignment of treatments, I estimate effects of three core elements of most monitoring and enforcement practices: self-reporting, audit frequency and specific deterrence. I find evidence of evasive reporting of violations in self-audits, as more violations are detected in on-site audits than in self-audits. Announcing the increased audit frequency has no effect on compliance, but an audit raises the firm's subsequent compliance substantially.
Keywords: K42; C93; Q58; D21; H41; 330; environmental regulation; enforcement; EPA; natural field experiment; random assignment